Optimized 3D Magnetization-Prepared Rapid Acquisition of Gradient Echo: Identification of Thalamus Substructures at 3T - Bender, B.; Mänz, C.; Korn, A.; Nägele, T.; Klose, U. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Because the substructures of the thalamus are not visible on standard T1- and T2-weighted MR images, planning of deep brain stimulation implantation relies on stereotactic atlas coordinates. The goal of the present work was to test whether an optimized 3D MPRAGE protocol can depict thalamus substructures. MATERIALS AND METHODS: After optimization of the TI to maximize contrast between gray matter and white matter, 6 healthy subjects were scanned at 3T with the optimized 3D MPRAGE. The results were compared with stereotactic atlases, and 2 expert readers trained in thalamic anatomy identified the 4 large thalamic nuclei groups. RESULTS: There was a high agreement between the different atlases and the resulting MR images. The 4 large thalamic nuclei groups (anterior, lateral, medial, posterior) could be detected reliably. The inter-reader consistency on the size and location was 75%–92%. CONCLUSIONS: The optimized 3D MPRAGE protocol improves contrast in the thalamus, and the 4 large thalamic nuclei groups can be identified with high inter-reader agreement. ACanterior commissureACPCanterior/posterior commissureCMcentre médian nucleusLDlateral dorsal nucleusMDmediodorsal nucleusMPRAGEmagnetization-prepared rapid acquisition of gradient echoPCposterior commissure